5-Iodo-1H-1,2,3-triazoles as Versatile Building Blocks - Danilkina, Natalia A.; Govdi, Anastasia I.; Balova, Irina A. (Synthesis, 2020)
Copper-catalyzed azide–alkyne cycloaddition is a useful tool for the synthesis of both 1,2,3-triazoles and 5-iodo-1H-1,2,3-triazoles starting from either terminal alkynes or iodoalkynes. 5-Iodotriazoles have been recognized as very useful building blocks for the synthesis of diverse 1,4,5-trisubstituted 1,2,3-triazoles. Synthetic application of 5-iodo-1,2,3-triazoles through the creation of a new C–C, C–heteroatom, or C–D(T) bond along with the application areas of both iodotriazoles and products of their modification including radiolabeled compounds are discussed.1 Introduction2 Synthetic Approaches to 5-Iodo-1H-1,2,3-triazoles3 5-Iodotriazoles in C–C Bond Formation3.1 Intermolecular C–C Cross-Coupling3.2 Intramolecular Cross-Coupling: Direct Arylation and C–I/C–I Homocoupling3.3 Other Transformations4 5-Iodotriazoles in Radiolabeling, Halogen Exchange, and Heterocoupling Reactions5 Summary
Keywords: CuAAC; 5-iodo-1,2,3-triazoles; iodoacetylenes; cross-coupling; hetero-coupling; halogen exchange; radiolabeling